1995
DOI: 10.1177/030098589503200501
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Ultrastructural Lesions of Idiopathic Cutaneous and Renal Glomerular Vasculopathy of Greyhounds

Abstract: Abstract. Idiopathic cutaneous and renal glomerular vasculopathy (CRGV) (Alabama rot) is a potentially fatal disease of unknown etiology that affects the skin and kidneys of racing-and training-age Greyhounds. Ultrastructural examinations were performed on two healthy control Greyhounds and 1 2 Greyhounds diagnosed with CRGV based on the presence of characteristic, well-demarcated cutaneous ulcers of the extremities (1 2/ 12), thrombocytopenia (<200,000 plateletddl) (1 2/12), and acute renal insufficiency (BUN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 21 publications
6
41
1
2
Order By: Relevance
“…15 Similar results were obtained in large animal models such as baboons 38 and dogs. 39 These latter models circumvent the mucosal innate immune response to bacterial colonization, which was more specifically addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similar results were obtained in large animal models such as baboons 38 and dogs. 39 These latter models circumvent the mucosal innate immune response to bacterial colonization, which was more specifically addressed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant animal models for E. coli O157:H7 infection are needed to study the physiological and pathological states of E. coli O157:H7 infectious disease in humans because of the difficulties associated with conducting clinical trials with humans. A wide variety of animal species, such as rabbits, dogs, and mice, have been used as models for human E. coli O157:H7 infections (3,8,10). For example, it has been reported that SLT-II isolated from E. coli O167:H7 induces colonic mucosal necrosis and hemorrhage, renal tubular necrosis, and lymphoid necrosis in various tissues in mice (4,25).…”
mentioning
confidence: 99%
“…Naturally occurring HUS-like disease has been described in greyhounds (15,23) and in rabbits (32). However, the association between the condition in dogs known as idiopathic cutaneous and renal glomerular vasculopathy and STEC has been neither fully established nor experimentally confirmed since these initial reports (15,43). The recent report of bloody diarrhea and HUS-like kidney lesions in laboratory rabbits from which unique STEC were isolated (15) may be a significant step toward the development of an animal model for HUS.…”
Section: Animal Models For Husmentioning
confidence: 99%